Assistive Robots for Home Healthcare: Exploring Proxemic Factors for Older Adults - Tsai, Yao-Lin; Mattas, Robert J.; Olatunji, Samuel A.; Rogers, Wendy A. (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
As the aging population grows, there is a shortage of caregivers, making assistive robots a promising solution to support older adults’ independence. Such robots would operate in close proximity to users, necessitating an understanding of appropriate distances to ensure comfort and predictable robot behavior. Proxemics, the study of personal space, plays a key role in designing robots that adapt to users’ preferences. We conducted a study with eleven older adults (age 62-77) to explore proxemic behaviors with an assistive robot in a simulated home environment. The robot performed two tasks: water bottle delivery and video calls. Video analysis focused on human behaviors and robot actions. Participants’ engagement varied as the robot moved through different proxemic zones. In social space, they oriented toward the robot and tracked its movements. As it entered personal space participant showed fewer visible reactions to the robot until it reached in the intimate space. These insights inform proxemic-based design considerations for assistive robots, enhancing user comfort and trust. Future work should explore proxemics and human behavior in a broad range of context, such as varied robot speed, direction, and notification, to better capture optimal robot assistant design for close-distance interactions with older adults in aging health care.